Genomic analysis of the aggressive tree pathogen Ceratocystis albifundus. Issue 5 (May 2019) - van der Nest, Magriet A.; Steenkamp, Emma T.; Roodt, Danielle; Soal, Nicole C.; Palmer, Marike; Chan, Wai-Yin; Wilken, P. Markus; Duong, Tuan A.; Naidoo, Kershney; Santana, Quentin C.; Trollip, Conrad; De Vos, Lieschen; et al.
Abstract: The overall goal of this study was to determine whether the genome of an important plant pathogen in Africa, Ceratocystis albifundus, is structured into subgenomic compartments, and if so, to establish how these compartments are distributed across the genome. For this purpose, the publicly available genome of C. albifundus was complemented with the genome sequences for four additional isolates using the Illumina HiSeq platform. In addition, a reference genome for one of the individuals was assembled using both PacBio and Illumina HiSeq technologies. Our results showed a high degree of synteny between the five genomes, although several regions lacked detectable long-range synteny. These regions were associated with the presence of accessory genes, lower genetic similarity, variation in read-map depth, as well as transposable elements and genes associated with host-pathogen interactions (e.g. effectors and CAZymes). Such patterns are regarded as hallmarks of accelerated evolution, particularly of accessory subgenomic compartments in fungal pathogens. Our findings thus showed that the genome of C. albifundus is made-up of core and accessory subgenomic compartments, which is an important step towards characterizing its pangenome. This study also highlights the value of comparative genomics for understanding mechanisms that may underly and influence the biology and evolution of pathogens. Highlights: Ceratocystis albifundus has a two-speed genome. Its genome consists of core and accessory subgenomic compartments. Genetic variation is linked to the presence and activity of transposable elements. Genome structure likely contributed to pathogenicity and host specialization.